POLITICS UKRAINIAN NATIONAL DEMOCRATIC ALLIANCE THE POLISH SEJM AND SENAT - Пуйда, Р. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Speech goes in the basic requirement Ukrainian Ambassadors - providing territorial autonomy to ethnic Ukrainian lands, which were in the Second Polish Republic. Anti-government stance provoked a number of critical performances member unit in late 1938 – early 1939, however, the unstable political situation in Europe, the growing tension in the central-eastern Europe were forced to UNDO in deliver a statement loyal to Poland that eventually must be secure against possible Polish Ukrainian destructions.